How Will Global Environmental Changes Affect the Growth of Alien Plants? - Jia, Jujie; Dai, Zhicong; Li, Feng; Liu, Yanjie (Frontiers in Plant Science, 2016)
Global environmental changes can create novel habitats, promoting the growth of alien plants that often exhibit broad environmental tolerance and high phenotypic plasticity. However, the mechanisms underlying these growth promotory effects are unknown at present. Here, we conducted a phylogenetically controlled meta-analysis using data from 111 published studies encompassing the responses of 129 alien plants to global warming, increased precipitation, N deposition, and CO2 enrichment. We compared the differences in the responses of alien plants to the four global environmental change factors across six categories of functional traits between woody and non-woody life forms as well as C3 and C4 photosynthetic pathways. Our results showed that all four global change factors promote alien plant growth. Warming had a more positive effect on C4 than C3 plants. Although the effects of the four factors on the functional traits of alien plants were variable, plant growth was mainly promoted via an increase in growth rate and size. Our data suggest that potential future global environmental changes could further facilitate alien plant growth.